المدارس التعليمية الرسمية في منطقة وادي العلندة إبتدائية اللموشي بنين 1964-1987 أنموذجاً - نعمي، أيمن, عطالله، عبد الباسط (جامعة الوادي university of Eloued, 2021)
الملخص: ان دراسة تاريخ التعليم الرسمي في منطقة وادي العلندة وتحديد المدرسة الابتدائية اللموشي بنين جعلتنا نتوصل للعديد من الملاحظات الهامة التي يمكننا حصرها في مايلي : - كانت منطقة وادي العلندة تتميز ببساطة الحياة في معاشهم ولباسهم حسب مايتلائم مع طبيعة المنطقة وخصوصيتها الصحراوية -عرفت منطقة وادي العلندة بالكثير من المساجد و انتشر بها التعليم القرآني من خلال الأئمة و الشيوخ و الطلبة المهتمين به كما ضمت العديد من الشخصيات و الرجال ، ساهموا بدورهم في تحفيظ وتعليم القرآن الكريم للأبناء من بينهم : بن عمر محمد الصالح، الشيخ الطالب أمحمد – الشيخ بنين البشير بن ابراهيم ...... وغيرهم. -كان للمدرسة تأثيرا كبيرا في واقع حياة سكان أهل وادي العلندة لأنها شكلت نواة التف حولها السكان من خلال تعليم أبنائهم بها. فأصبحت جذابة من أجل التعليم والرقي في مداركه واستطاع الكثير ممن درسوا بها أن يصبحوا لاحقا اطارات في مختلف المجالات كالتعليم بأطواره المختلفة و الطب و الهندسة ....وغيرها. -استطاعت الدرسة استقطاب عدد معتبر من البنات منذ التأسيس وتمكنت من تغيير ولو بشكل نسبي نظرة المحتمع لتعليم الفتاة و فتح المجال أمام تعلم البنات . -إن سجلات القيد الخاصة بمدرسة اللموشي بنين بوادي العلندة، تثبت بأن ادارة المردسة لم تحدد بنينا معين للالتحاق بها في بداية تأسيسها ، كما فتحت المدرسة أبوابها لمختلف طبقات المجتمع ولم تضع أي معايير لذلك ، عرفت المدرسة الابتدائية اللموشي بنين بوادي العلندة تطورا مع الزمن شمل هيكلها وعدد الحجرات الدراسية و ارتفاعاً مطردا في عدد المعلمين و التلاميذ. لقد كان للمدرسة تأثير ثقافي على التلاميذ بها و نلتمس بالإضافة الى اللغة، فأصبحوا يجدون التكلم باللغة العربية الفصحة و اللغة الفرنسية بطلاقة وعموما فأن المدرسة الابتدائية للموشي بنين بوادي العلندة ورغم كل العراقيل التي واجهتها لعبت دوراُ كبيراً في حياة المجتمع و توعيته من خلال التعليم والارشاد واخراج الكثير من أهل المنطقة من غياهب الجهل الى نور العلم. الكلمات المفتاحية: - المدرسة - وادي العلندة - التعليم - اللموشي بنين ABSTRACT: Studying the history of formal education in the Wadi Al-Alanda region and identifying the Lamushi primary school for boys made us reach many important observations that we can summarize in the following: The Wadi Al-Allanda region was characterized by the simplicity of life in their livelihood and clothing, according to what suited the nature of the region and its desert specificity. The area of Wadi Al-Alanda was known for many mosques, and Quranic education spread through it through imams, sheikhs, and students interested in it. It also included many personalities and men, who in turn contributed to memorizing and teaching the Noble Qur’an to children, including: Bin Omar Muhammad Al-Saleh, Sheikh Al-Talib Muhammad - Sheikh Benin Al-Bashir Bin Ibrahim ... and others. The school had a great impact on the reality of the lives of the people of Wadi Al-Alanda, because it formed a nucleus around which the population gathered by educating their children. It became attractive for the sake of education and advancement in its awareness, and many of those who studied there were able to later become tires in various fields such as education in its various stages, medicine and engineering .... and others. - The study was able to attract a significant number of girls since its establishment and was able to change, even in a relative way, the society's view of girls' education and open the way for girls' education. - The enrollment records of Al-Lamushi Boys School in Wadi Al-Alanda prove that the school administration did not specify specific boys to join it at the beginning of its establishment, and the school opened its doors to the various classes of society and did not set any criteria for that. The Allamushi Primary School for Boys in Wadi Allanda has known a development over time, including its structure, the number of classrooms, and a steady increase in the number of teachers and students. The school had a cultural impact on the students, and in addition to the language, they find that they can speak fluent Arabic and French fluently. In general, the elementary school of Al-Mushi for Boys in Wadi Al-Alanda, despite all the obstacles it faced, played a major role in the life of the community, raising its awareness through education and guidance, and bringing many of the people of the region out of ignorance into the light of knowledge.+ key words:  School  Wadi Al-Andah  Education  Lamushi Benine
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي الحديث و المعاصر
Keywords: التعليم بوادي العلندة; L'éducation dans la Vallée d'Allanda; Education in the Valley of Allanda